Masculinity; the source of conflict between doctors and managers in the NHS? A study of contemporary cultural influences on the identity constructions of senior consultants. - Doyle, E. K. (2009)
This dissertation examines the nature of the relationship between doctors and managers. Since the introduction of general management in the 1980s there has been a substantial body of literature discussing the two groups and suggesting improvements. This research looks at the problem from a fresh perspective by considering masculinity as the source of the poor relationships. By examining doctors’ talk in regards to contemporary cultural influences which affect our modern conceptions of masculinity, this research offers an analysis that suggests these doctors take great pains to construct a powerful self image of masculinity in the face of the threat posed by management. This study opens up new possibilities for the understanding of the relationships between doctors and managers.